Metodologi dan Karakteristik Penafsiran Ahmad Mustafa Al Maraghi Dalam Kitab Tafsir Al Maraghi: (Kajian Atas QS. Al Hujurat Ayat: 9) - Fithrotin Fithrotin (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2018)
The commentary of al-Maraghi by Ahmad Musthofa al Maraghi is one of the best interpretive books in the modern century. The author of the book implicitly can be seen in the preamble of the interpretation that the interpretation of the book is influenced by two factors, namely external and internal factors. The style and color of the interpretation of the book offers a very simple writing system and a pattern of sentence editorial arrangements that is easily understood by maintaining consistency and systematic problem exposure within the scope of the discussion themes which are parsed with the ability and capability of the author's knowledge, which begins with expressing verses at the beginning of the discussion, explain the vocabulary, explain the meaning of the verse globally, and explain asbab al-nuzul ayat.